Central Sulawesi Grand Forest Park: “Participatory Mapping Model for Conflict Resolution on Forest Resource Utilization” - Hasriani Muis; Golar; Arman Maiwa; Abdul Rahman; Hauris; Wahyu Syahputra Simorangkir (Jurnal Penelitian Pendidikan IPA, 2025)
Land claims and forest resource utilization activities are one of the causes of conflict in forest management in the Grand Forest Park (Tahura) area of ​​Central Sulawesi. The existence of communities around and within the Central Sulawesi Grand Forest Park is an inseparable part of forest ecosystem management. The success of management planning for it will be more achieved if the manager has reliable instruments and strategies in dealing with problems and conflicts between forest managers and the community. The aim of the research is to classify the roles of the parties in the utilization of forest resources in Tahura and to design a participatory mapping model for conflict resolution over the use of forest resources in Tahura. The research method used in this research is a matrix of interrelationships between stakeholder issues to determine conflict issues on a priority scale, stakeholder analysis to map the influence and interests of stakeholders and to determine a participatory conflict resolution mapping model using a soft system method. Focusing on conflict issues that are on the priority scale, namely land (tenurial) conflicts and conflicts over the value of the benefits of the existence of Tahura. The results of stakeholder mapping related to land conflict resolution consist of: key actors (key players) including: Central Sulawesi Forestry Service, UPTD Tahura, Village Communities, and Forest Farmer Groups. Meanwhile, the resolution model formulated is "Joint control" based on the role of each stakeholder, namely the Management body or Advisor Body.